Security issues of ad-hoc network of sensor node in disaster mitigation plan - Sameon S.S.; Jamil N. (American Scientific Publishers, 2023)
The functionality and capability of communication infrastructures may be reduced or totally destroyed in disaster. This could lead to very difficult and complicated situations to be handled by the authorities and the rescue teams especially for them to detect, locate and save the survivors. This paper discuss on focusing the security issues of Ad-hoc Network of Sensor Node for Communication Infrastructures during natural disaster. The inclusion of wireless communication technology also incurs various types of security threats. Moreover, wireless sensor networks are vulnerable because nodes are often placed in a hostile or unsecured environment where they are not physically protected. The identified security threats then will be match with the proposed defense mechanisms in order to plan the mitigation of disaster using Wireless Sensor Node. 2015 American Scientific Publishers. All rights reserved.